Análisis de los riesgos laborales presentes en la empresa LÁCTEOS EL ROSARIO AD SAS (2021)
Nowadays it is vital that every company has an occupational health and safety management system, every management system must have a series of requirements to generate a healthy work environment with optimal conditions. Therefore, this project highlights the importance of the identification and assessment of occupational risks, which aims to analyze the risk factors to which the workers of the company Lacteous elRosario AD S.A.S. By complying with these requirements, it is possible to control risks and accidents, in addition to improving the performance of workers along with greater safetywhen carrying out their daily tasks. To carry out this research, physical, mechanical, biological, biomechanical riskfactors, among others, were analyzed. For this analysis carried out we are based on theColombian technical standard GTC 45, which allowed us to identify, analyze and evaluate each of the risks that arise in the company in order to take preventive and corrective action measures to improve working conditions within of the company. Keywords: Hazard identification, risk assessment